tudy on optimum condition of empty fruit bunch-graft-acrylic acid superabsorbent polymer composites - Mohammad Amar, Mohammad Ali (2013)
Oil palm empty fruit bunch graft (acrylic acid) superabsorbent composite (OPEFB-g-AA SPC) was synthesized by graft copolymerization of the acrylic acid (AA) comonomer onto OPEFB fibre using ammonium persulfate (APS) and N,N-methylene bisacarylamide (MBA) as an initiator and crosslinker. Systematically, variables that affect the swelling behaviors of OPEFB-g-AA SPC were optimized. The effects of initiator, crosslinker and filler concentration as well as solvent quantity and the degree of neutralization on water absorbency of OPEFB-g-AA SPC were studied. Maximum absorbency of OPEFB-g-AA SAPC was achieved in the range at 200 g/g – 250 g/g when the amount of APS and MBA were 0.8 wt.% and 1.0 wt.%, respectively, and the OPEFB loading was at 10 wt.%. The chemical structure of the OPEFB-g-AA SPC was characterized by means of Fourier transform infrared (FTIR) spectroscopy and Thermogravimetric Analysis (TGA) were carried out to confirm the chemical structure and thermal properties of the synthesized superabsorbent.